Influence of different drugs on HIV risk in people who inject: systematic review and meta‐analysis. (15th March 2015) - Tavitian‐Exley, Isabel; Vickerman, Peter; Bastos, Francisco I.; Boily, Marie‐Claude
Abstract: Aims: To assess systematically the risk of HIV acquisition by type of drug injected across different settings. Methods: A systematic review and meta‐analysis were conducted. Databases were searched for studies of HIV incidence in people who inject different drugs (PWID). Pooled HIV incidence rate ratio (IRR) was used to compare HIV risk between injecting and not‐injecting a given drug, when possible, or otherwise with those reported not to have injected the substance. Pooled estimates of crude IRR were derived using random‐effects models. Variations in IRR were assessed in subgroup analyses, by drug and geographical region. Results: Of 5779 studies screened, 15 were included. HIV incidence was reported for people injecting cocaine (eight: North America, Europe), amphetamine‐type stimulants (ATS) (four: Western and Eastern Europe, Asia), heroin (11: all settings), opiate‐stimulants (four: North America, Western and Eastern Europe) and opiates–sedatives (five: Europe, Asia). HIV risk in cocaine injectors was 3.6 times 95% confidence interval (CI) = 2.8–4.7, I 2  = 0%; n  = 4) that of non‐injectors and 3.0 for ATS injectors (95% CI = 2.2–4.1, I 2  = 0%; n  = 2). Higher sexual risk was reported in cohorts injecting stimulants. Compared to not‐injecting, HIV IRR was 2.8 (95% CI = 1.7–4.7, I 2  = 77%; n =6) for all heroin injectors and 3.5 (95% CI = 2.3–5.2, I 2  = 40%; n =5) for heroin injectors in Asia and Europe. Conclusion: The risk of HIV acquisition in people who inject drugs appears to vary by drug type but differences are not statistically significant, precluding conclusive grading of risk.